Environmentally friendly thermoelectric sulphide Cu2ZnSnS4 single crystals achieving a 1.6 dimensionless figure of merit ZT. Issue 28 (23rd June 2021) - Nagaoka, Akira; Yoshino, Kenji; Masuda, Taizo; Sparks, Taylor D.; Scarpulla, Michael A.; Nishioka, Kensuke
Abstract : A record high dimensionless figure of merit ZT = 1.6 has been achieved in totally environmentally benign Cu2 ZnSnS4 (CZTS) single crystal. Abstract : Thermoelectrics (TEs) are an important class of technology that harvest electric power directly from heat sources. When designing both high performance and environmentally friendly TE materials, the pseudo-cubic structure has great theoretical potential to maximize the dimensionless figure of merit ZT . The TE multinary single crystal with a pseudo-cubic structure paves a new path toward manipulating valley degeneracy and anisotropy with low thermal conductivity caused by short-range lattice distortion. Here, we report a record high ZT = 1.6 around 800 K realized in a totally environmentally benign p-type Na-doped Cu2 ZnSnS4 (CZTS) single crystal. The exceptional performance comes from a high power factor while maintaining intrinsically low thermal conductivity. The combination of the pseudo-cubic structure and intrinsic properties of the CZTS single crystal takes advantage of simple material tuning without complex techniques.